Pengaruh Kompensasi, Motivasi dan Komitmen Organisasional terhadap Kinerja Karyawan bagian Akuntansi - Zulifah Chikmawati (Politeknik Ganesha Medan, 2019)
The era of globalization encourages companies to self-improvement in order to compete and retain its life. Required the presence of a strategic plan to implement them. Therefore, the role of accounting in a company that is indispensable in terms of decision making. Employees of the accounting department tends to have high job stress as part of their time is spent in the workplace and in the same occupation. In general, the performance of employees believed to be influenced by compensation, motivation and commitment from employees themselves, such performance will ultimately have an impact on organizational performance.To determine whether the compensation, motivation, and organizational commitment have a significant effect on the performance of the accounting employee on manufacturing companies producing footwear in Surabaya, the research was conducted. The method used in this study is the multiple linear regression. Data used in this study is the result of primary data questionnaire with 32 respondents.Having done the analysis and discussion, it was found that the partial conclusion, motivation significantly influence employee performance, compensation and organizational commitment whereas no significant effect on employee performance. Era globalisasi mendorong perusahaan untuk meningkatkan dan menjalani kehidupan mereka. Diperlukan adanya rencana strategis untuk mengimplementasikannya. Karena itu, peran keputusan dibuat dalam hal pengambilan keputusan. Karyawan departemen akuntansi cenderung memiliki stres kerja yang tinggi sebagai bagian dari waktu kerja dan dalam pekerjaan yang sama. Secara umum, kinerja karyawan diyakini dipengaruhi oleh kompensasi, motivasi dan komitmen dari karyawan itu sendiri, kinerja tersebut pada akhirnya akan berdampak pada kinerja organisasi, baik apakah kompensasi, motivasi, dan komitmen organisasi memiliki pengaruh yang signifikan terhadap kinerja karyawan. karyawan akuntansi pada perusahaan manufaktur di Surabaya, penelitian ini dilakukan. Metode yang digunakan untuk penelitian ini adalah regresi linier berganda. Ditemukan bahwa kesimpulan parsial, motivasi, dan pengaruh kinerja karyawan, kompensasi dan komitmen organisasi, sedangkan berpengaruh tidak signifikan terhadap kinerja karyawan.